Editorial - Nsamu Moonga; Vasintha Pather; Lireko Qhobela (South African Journal of Arts Therapies)
The late Zulu sangoma and keeper of African wisdom, Credo Mutwa, once reflected on a profound moment of healing that challenged his understanding of therapeutic intervention. Having exhausted Western medical approaches to address his psychological distress following a violent attack in 1937, it was his grandfather, a man dismissed by missionaries as an ‘ungodly heathen’, who ultimately restored him to health (Mutwa, 1964). This experience led Mutwa (1964) to question why those dismissed by missionaries as ‘ungodly heathens’ possessed healing knowledge that Western medicine lacked. This poignant reflection encapsulates the central tension that this special issue of the South African Journal of Arts Therapies seeks to address.